THE ROLE OF PHYSIOTHERAPY IN ACHIEVING HIGH LEVEL OF PUBLIC HEALTH - Rima Yunita Sari; Rizqi Amalia Solichati; Putra Yudha Wahyu (Journal of Community Research and Engagement, 2025)
Background: Physiotherapy plays a crucial role in improving public health, focusing on maintaining and enhancing movement and body function, targeting healthy individuals to prevent disease. Physiotherapy services encompass not only curative and rehabilitative services but also preventive and promotive services within the community. Objectives: This community service aimed to educate public about physiotherapy and targeted individuals with movement and functional impairments in their daily activities. Method: This community service activity method was used to solve problems through a socialisation and education approach. Direct outreach and education were provided to the community through face-to-face consultations and discussions. Results: Based on the findings, it was found that many people are still unaware of the disorders they experience and the initial treatment to overcome them, as well as the role of physiotherapy in addressing these problems. The implementation of this activity is very important and necessary in achieving a high level of public health, starting with addressing problems of movement and functional disorders. Conclusion: This community is provided with knowledge through socialisation and provided with physiotherapy services for problems that result in movement and function disorders faced in daily activities. Keywords: Education; Physiotherapy; Public Health; Socialization